2019
DOI: 10.4103/ija.ija_48_19
|View full text |Cite
|
Sign up to set email alerts
|

McGrath MAC video laryngoscope versus direct laryngoscopy for the placement of double-lumen tubes: A randomised control trial

Abstract: Background and Aims: Role of video laryngoscopes (VLs) in the management of difficult airway with single-lumen tubes (SLTs) is established. VLs provide improved glottis view but are associated with longer time to intubate (TTI). We aimed to compare the TTI for double-lumen tube (DLT) insertion using the McGrath ® MAC VL versus direct Macintosh laryngoscope (DL). Methods: Eleven senior anaesthesiologists experienced in SLT insertion, but not DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
2
21
0
1
Order By: Relevance
“…The results are similar to other studies where videolaryngoscopes where used to facilitate endotracheal intubation [20,21]. Bakshi et al compared the time to intubation for double-lumen tube insertion using the McGrath® MAC VL versus direct Macintosh laryngoscope and revealed that this parameter was similar on both groups, however videolaryngoscopy was associated with better glottis visualization, reduced need of external laryngeal manipulation and fewer complications [22].…”
Section: Discussionsupporting
confidence: 83%
“…The results are similar to other studies where videolaryngoscopes where used to facilitate endotracheal intubation [20,21]. Bakshi et al compared the time to intubation for double-lumen tube insertion using the McGrath® MAC VL versus direct Macintosh laryngoscope and revealed that this parameter was similar on both groups, however videolaryngoscopy was associated with better glottis visualization, reduced need of external laryngeal manipulation and fewer complications [22].…”
Section: Discussionsupporting
confidence: 83%
“…For incomplete outcome data report, Twenty-two studies (96%) reported the completeness of outcome data for each main outcome and were assessed as having a low risk of bias. One study (4%) checked as unclear risk [32]. All studies (100%) were assessed as having a low risk of bias about Selective reporting and Other potential sources of bias.…”
Section: Plos Onementioning
confidence: 99%
“…Success rate of the first attempt intubation of DLT. Four groups of devices from 21 studies were available for the analysis [1,7,8,17,18,20,[24][25][26][27][28][29][30][31][32][33][35][36][37][38][39]. Eligible comparisons in the NMA are shown in Figs 3A and 4A.…”
Section: Primary Endpointmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have found that VL improves the ability to visualize the larynx and improves the intubation success. [ 4 5 6 7 ]…”
Section: Introductionmentioning
confidence: 99%